Progress and perspectives in the electroreduction of low-concentration nitrate for wastewater management - Kouer Zhang; Xiaohong Zou; Yun Liu; Xiao Zhang; Liang An (iScience)
Summary: The electroreduction of nitrate has emerged as a promising global strategy for water purification in the face of harmful nitrate in wastewater. However, the usually low concentration of nitrate in wastewater poses a great challenge to this process, thus necessitating more in-depth studies to optimize its efficiency. This perspective article briefly explores the various electrochemical pathways of nitrate reduction, including the conversion of nitrate to ammonia, the conversion of nitrate to dinitrogen, and the C-N coupled reduction process. In addition, the feasibility of the electroreduction method is assessed from the concentration nitrate sources, reactor design, and promising energy sources, while also offering insights into prospective developments for further research.